Identification and functional analysis of peroxiredoxin isoforms in Euglena gracilis. Issue 4 (3rd April 2014) - Tamaki, Shun; Maruta, Takanori; Sawa, Yoshihiro; Shigeoka, Shigeru; Ishikawa, Takahiro
Abstract: Euglena gracilis lacks catalase and contains ascorbate peroxidase (APX) which is localized exclusively in the cytosol. Other enzymes that scavenge reactive oxygen species (ROS) in Euglena have not yet been identified; therefore, ROS metabolism, especially in organelles, remains unclear in Euglena . The full-length cDNAs of four Euglena peroxiredoxins ( EgPrxs ) were isolated in this study. EgPrx1 and -4 were predicted to be localized in the cytosol, and EgPrx2 and -3 in plastids and mitochondria, respectively. The catalytic efficiencies of recombinant EgPrxs were similar to those of plant thiol-peroxidases, but were markedly lower than those of APX from Euglena . However, transcript levels of EgPrx1, -2, and -3 were markedly higher than those of APX . The growth rate of Euglena cells, in which the expression of EgPrx1 and -4 was suppressed by gene silencing, was markedly reduced under normal conditions, indicating physiological significance of Prx proteins. Graphical abstract: : Four peroxiredoxin (Prx) isoforms were identified and ascertained to be functional peroxidases as well as ascorbate peroxidase (APX) in a photosynthetic protist, Euglena gracilis .